The Multifaceted Impact of Directors and Officers Insurance on Corporate Governance and Performance - Xue Chang (Asian Academy of Management Journal of Accounting and Finance, 2024)
In the ever-evolving capital market, safeguarding shareholder rights and interests is paramount for Chinese listed companies facing escalating risks. This article explores the dynamic discourse surrounding Directors and Officers (D&O) insurance, focusing on its implications in emerging markets with lower institutional support and disclosure quality. Spanning 2000 to 2020, this study rigorously examines the impact of D&O insurance in China, investigating its associations with capital markets, regulatory frameworks, managerial practices and financial reporting. My analysis reveals that D&O insurance correlates negatively with CEO turnover and litigation risk. However, its influence on investment efficiency, earnings management, financial reporting and corporate governance is comparatively modest. I also uncover nuanced disparities between stateowned enterprises (SOEs) and non-state-owned enterprises (non-SOEs). In SOEs, where CEOs are appointed by the government and litigation risk is lower, D&O insurance’s impact is less pronounced. Conversely, non-SOEs, facing higher litigation risk, find greater significance in D&O insurance as protection against legal action. In summary, this article highlights D&O insurance’s role as a protective shield for CEOs and underscores its evolving dynamics in Chinese listed companies’ corporate governance and risk management.